Weather-resistant transparent adhesive, preparation method and application of weather-resistant transparent adhesive to adhesion of weather-resistant and wear-resistant transparent film and color-coated sheet

By preparing weather-resistant transparent adhesives, using the reaction of intermediate products A and B, as well as the use of nano zinc oxide and surface modifiers, the epoxy resin is modified, and the epoxy resin adhesive is solved under mechanical stress The problem of easy destruction and reduced transparency achieves high toughness, excellent transparency and UV resistance.

CN119432279AActive Publication Date: 2025-02-14LORICA NEW MATERIAL TECH (JIANGSU) CO LTD

Patent Information

Application Number
CN202411549264.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-14
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

Existing epoxy resin adhesives are prone to early damage under mechanical stress, and the addition of fillers leads to a decrease in transparency, which cannot meet the application that requires transparency.

Method used

By preparing a weather-resistant transparent adhesive, reacting 4-(2,3-ethylene oxide)benzaldehyde with tetrakis(3-mercaptopropionate)pentaerythritol ester to obtain intermediate product A and with 4,5-diphenyl The aminobenzene-1,2-diphenol reaction forms intermediate product B. Then, an organic-inorganic hybrid curing agent is used to form a nano zinc oxide and a surface modifier, and the epoxy resin is modified in combination with a composite modifier to form a modified epoxy resin.

Benefits of technology

It improves the toughness, strength, transparency and anti-ultraviolet aging properties of epoxy resin, and meets the bonding needs of weather-resistant and wear-resistant transparent films and color-coated boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432279A_ABST
    Figure CN119432279A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and discloses a weather-resistant transparent adhesive, a preparation method and application of the weather-resistant transparent adhesive to adhesion of a weather-resistant and wear-resistant transparent film and a color-coated sheet. The preparation method of the weather-resistant transparent adhesive comprises the following steps: reacting 4-(2, 3-ethylene oxide) benzaldehyde with tetrakis (3-mercaptopropionic acid) pentaerythritol ester to obtain an intermediate product A; reacting the intermediate product A with 4, 5-diaminobenzene-1, 2-diphenol to obtain an intermediate product B; preparing nano zinc oxide, performing surface modification on the nano zinc oxide, and grafting the intermediate product B to obtain an organic-inorganic hybrid curing agent; modifying epoxy resin by using the composite modifier to obtain modified epoxy resin; the modified epoxy resin, the organic-inorganic hybrid curing agent and the accelerant are mixed and stirred, and the weather-resistant transparent adhesive is obtained; the weather-resistant transparent adhesive disclosed by the invention is high in transparency and has excellent mechanical strength, toughness, adhesiveness and weather resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a weather-resistant transparent adhesive, a preparation method and application of the adhesive in bonding weather-resistant and wear-resistant transparent films and color-coated plates. Background Art

[0002] Because epoxy resin adhesive has excellent bonding ability, good mechanical strength and thermal stability, it is often used in various industries and can also be used for bonding color coated plates with other materials. However, the toughness and weather resistance of epoxy resin adhesive are poor, and it is easy to be damaged early under mechanical stress, which limits its application. In order to solve the above problems, Chinese patent application CN101457132A provides a high-toughness epoxy adhesive, whose components and component weight ratio are: epoxy resin: nitrile rubber = 5: 1-12: 1, and bisphenol A epoxy resin E-44 and E-51 with excellent performance are selected as the main resins, and on the basis of the existing formula, nitrile-40 liquid rubber and carboxyl-terminated liquid nitrile rubber (CTBN) are used to toughen the curing system under the condition of room temperature curing.

[0003] Chinese patent application CN103382378A provides a weather-resistant epoxy adhesive, characterized in that it is prepared by mixing component A and component B, and the mixing ratio of component A to component B by weight is 1:1. The preparation method of the weather-resistant epoxy adhesive improves the weather resistance of the epoxy adhesive by adding a light stabilizer and an ultraviolet absorber.

[0004] However, the above technical solutions cannot take into account both the toughness and weather resistance of the adhesive at the same time, and in the process of modifying the adhesive, the addition of fillers often leads to a decrease in the transparency of the adhesive, making the adhesive unsuitable for use in work environments that require transparency. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a weather-resistant transparent adhesive, comprising the following steps:

[0006] Step (1), 4-(2,3-ethylene oxide)benzaldehyde reacts with pentaerythritol tetrakis(3-mercaptopropionic acid) to obtain an intermediate product A; intermediate product A reacts with 4,5-diaminobenzene-1,2-diphenol to obtain an intermediate product B;

[0007] Step (2), using zinc nitrate and sodium carbonate as raw materials to prepare nano zinc oxide;

[0008] Nano zinc oxide is surface-modified by 3-glycidyloxypropyltrimethoxysilane and grafted with intermediate product B to obtain an organic-inorganic hybrid curing agent;

[0009] Step (3), modifying the epoxy resin with a composite modifier to obtain a modified epoxy resin; using the modified epoxy resin as component A; mixing an organic-inorganic hybrid curing agent and an accelerator DMP-30 as component B; wherein the preparation method of the composite modifier comprises the following steps:

[0010] Step S1, acrylic acid, 1,4-pentadiene, dodecafluoroheptyl methacrylate, and butyl acrylate are polymerized to obtain a tetrapolymer; glycidyl POSS and 1,4-butanedithiol are reacted to obtain modified POSS; the tetrapolymer is reacted with the modified POSS to obtain a grafted modified POSS;

[0011] Step S2: reacting the graft-modified POSS with 4,4'-dithiodiphenylamine to obtain a composite modifier.

[0012] When using, mix components A and B and stir.

[0013] Preferably, in the step (1), the preparation method of the intermediate product A is as follows: 4-(2,3-ethylene oxide)benzaldehyde is added to ethyl acetate, stirred for 20-30 minutes to obtain a mixed solution; after mixing pentaerythritol tetrakis(3-mercaptopropionic acid) ester and triethylamine, the mixed solution is added dropwise at a rate of 0.8-1.2 mL / min, the temperature is raised to 65-75°C, the reaction is stirred for 16-20 hours, and the intermediate product A is obtained by rotary evaporation at 70-80°C; wherein the mass ratio of 4-(2,3-ethylene oxide)benzaldehyde, ethyl acetate, pentaerythritol tetrakis(3-mercaptopropionic acid) ester and triethylamine is (8.9-17.8):(400-500):(24.4-48.8):(0.5-0.8);

[0014] In the above process, the epoxy group of 4-(2,3-ethylene oxide)benzaldehyde is ring-opened to react with the thiol group of pentaerythritol tetrakis(3-mercaptopropionate), and the thiol group of pentaerythritol tetrakis(3-mercaptopropionate) is chain-extended and modified. The chain extension of 4-(2,3-ethylene oxide)benzaldehyde provides the reactive group aldehyde group for the intermediate product A.

[0015] Preferably, in the step (1), the preparation method of the intermediate product B is as follows: adding the intermediate product A to ethanol, stirring for 20-40 minutes, then adding 4,5-diaminobenzene-1,2-diphenol, heating to 60-75°C and stirring for reaction for 3-5 hours, after the reaction is completed, standing, centrifuging, and drying to obtain the intermediate product B; wherein the mass ratio of the intermediate product A, ethanol, and 4,5-diaminobenzene-1,2-diphenol is (8.3-16.6):(100-120):(3.5-7);

[0016] In the above process, an amino group in 4,5-diaminobenzene-1,2-diphenol reacts with the aldehyde group of intermediate product A, introducing a catechol group and a dynamic imine bond into intermediate product B;

[0017] Preferably, in the step (2), the preparation method of the nano zinc oxide is as follows: preparing a zinc nitrate aqueous solution and a sodium carbonate aqueous solution with a concentration of 0.2 mol / L each, adding the zinc nitrate aqueous solution to the sodium carbonate aqueous solution at a speed of 1-1.5 mL / min at a stirring speed of 400-500 r / min, filtering, washing, drying, and finally calcining at 300-350° C. for 2 h to obtain nano zinc oxide with an average particle size of 22.2-26.7 nm; wherein the volume ratio of the zinc nitrate aqueous solution to the sodium carbonate aqueous solution is 5:6;

[0018] In the above process, zinc nitrate and sodium carbonate are used as raw materials to prepare nano zinc oxide, and the calcination temperature is controlled to be 300-350° C. The average particle size of the obtained nano zinc oxide is 22.2-26.7 nm. When the nano zinc oxide in this particle size range is added to the epoxy resin material at a low content, it has high visible light transparency and high ultraviolet shielding efficiency (an average particle size of the nano zinc oxide that is too large will reduce the transparency of the epoxy resin material, and a particle size that is too small will cause its ultraviolet shielding efficiency to decrease);

[0019] Preferably, in step (2), the preparation method of the organic-inorganic hybrid curing agent is:

[0020] 3-glycidyloxypropyltrimethoxysilane, nano zinc oxide, and ethanol are mixed in a mass ratio of (1-3):(10-12):(100-120), and then refluxed at 75-80° C. and a pH value of 4-10 for 4-6 hours, and the precipitate is collected and dried to obtain surface-modified nano zinc oxide;

[0021] Add the surface modified nano zinc oxide to N,N-dimethylformamide, ultrasonically treat for 30-40 minutes, then add the intermediate product B, heat to 75-85°C, stir and react for 22-26 hours, filter, wash and dry after the reaction to obtain an organic-inorganic hybrid curing agent; wherein the mass ratio of the surface modified nano zinc oxide, N,N-dimethylformamide and the intermediate product B is (8-10):(120-150):(3-5);

[0022] In the above process, 3-glycidyloxypropyltrimethoxysilane is used to modify the surface of nano-zinc oxide, and epoxy groups are introduced on the surface of nano-zinc oxide. The epoxy groups then react with the remaining amino groups in the intermediate product, and the nano-zinc oxide is combined with the intermediate product B to obtain an organic-inorganic hybrid curing agent.

[0023] Preferably, in step (3), the preparation method of the modified epoxy resin is as follows: adding the composite modifier to N,N-dimethylformamide, stirring for 20-30 minutes, then adding the epoxy resin, reacting in a water bath at 75-85°C for 1.5-2.5 hours, and after the reaction is completed, removing the solvent by rotary evaporation at 75-85°C to obtain the modified epoxy resin; wherein the mass ratio of the composite modifier, N,N-dimethylformamide, and the epoxy resin is (1.5-3.5):(100-200):(50-80);

[0024] In the above process, the epoxy groups in the epoxy resin react with the amino groups in the composite modifier, and a side chain containing the composite modifier structure is introduced into the epoxy resin;

[0025] Preferably, in step (3), the mass ratio of the organic-inorganic hybrid curing agent to the accelerator DMP-30 is 1:(0.03-0.07); the mass ratio of component A to component B is 1:(1-1.25); and the stirring conditions are: stirring at a speed of 150-250 r / min for 2-5 min.

[0026] Furthermore, in step (3), the preparation method of the composite modifier is:

[0027] Step S1, mixing acrylic acid, 1,4-pentadiene, dodecafluoroheptyl methacrylate, butyl acrylate, ammonium persulfate, and N,N-dimethylformamide in a mass ratio of (3.6-7.2):(3.4-6.8):(0.3-0.8):(6.4-12.8):(0.07-0.1):(80-100), reacting at 70-90° C. for 2-4 hours, centrifuging, washing, and drying after the reaction to obtain a tetrapolymer;

[0028] Add glycidyl POSS to a mixed solution of ethanol and acetone, stir at room temperature until the mixed solution is colorless and transparent, then add 1,4-butanedithiol and triethylamine, heat to 75-85°C in a closed environment and react for 5-7h, and after the reaction is completed, distill to obtain modified POSS; wherein the mixed solution of ethanol and acetone is obtained by mixing ethanol and acetone in a mass ratio of 3:1; the mass ratio of glycidyl POSS, the mixed solution of ethanol and acetone, 1,4-butanedithiol, and triethylamine is (10-12):(60-100):(1.2-1.5):(0.8-1.2);

[0029] Add the tetrapolymer and azobisisobutyronitrile to tetrahydrofuran, stir until the solid is completely dissolved, heat to 55-65°C in a nitrogen atmosphere, and dropwise add a modified POSS / tetrahydrofuran mixture with a concentration of 0.2 g / mL within 10-15 minutes under stirring, keep the temperature unchanged and react for 5.5-6.5 hours. After the reaction is completed, concentrate the reaction mixture to one third of the original volume, add methanol to precipitate the product, filter, and dry to obtain graft-modified POSS; wherein the mass ratio of the tetrapolymer, azobisisobutyronitrile, tetrahydrofuran, and modified POSS / tetrahydrofuran mixture is (9.2-18.4):(0.5-1.0):(40-70):(27.5-55);

[0030] In the above process, acrylic acid, 1,4-pentadiene, and dodecafluoroheptyl methacrylate are polymerized under the initiation of ammonium persulfate to form a tetrapolymer containing carboxyl groups, carbon-carbon double bonds, fluorinated alkyl chains, and flexible alkyl chains; a small amount of epoxy groups in the glycidyl POSS react with the thiol groups at one end of 1,4-butanedithiol to introduce thiol groups into the glycidyl POSS to obtain modified POSS; further, the thiol groups in the modified POSS react with the carbon-carbon double bonds in the tetrapolymer to undergo a thiol-ene click reaction to introduce polymer chains into the glycidyl POSS;

[0031] Step S2, adding the grafted modified POSS to methanol, ultrasonically treating for 30-40 minutes, then adding 4,4'-dithiodiphenylamine, stirring for 10-20 minutes, and then dripping 1-ethyl-(3-dimethylaminopropyl)carbodiimide / methanol solution with a concentration of 0.07 g / mL at a rate of 0.8-1.2 mL / min while stirring at room temperature, stirring for 22-26 hours, standing for 6-8 hours, filtering, washing, and drying to obtain a composite modifier; wherein the amount ratio of the grafted modified POSS, methanol, 4,4'-dithiodiphenylamine, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide / methanol solution is (5-10) g:(400-500) g:(1.5-3.5) g:(10-20) mL;

[0032] In the above process, the carboxyl group in the polymer chain on the graft-modified POSS undergoes an amidation reaction with the amino group of 4,4'-dithiodiphenylamine, and 4,4'-dithiodiphenylamine containing a dynamic disulfide bond is introduced into the graft-modified POSS.

[0033] The weather-resistant transparent adhesive is prepared by the method for preparing the weather-resistant transparent adhesive.

[0034] The weather-resistant transparent adhesive is used for bonding weather-resistant and wear-resistant transparent films and color-coated plates.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The invention modifies glycidyl POSS, grafts a tetrapolymer and 4,4'-dithiodiphenylamine to obtain a composite modifier, and then uses the composite modifier to graft and modify epoxy resin to obtain a modified epoxy resin; wherein the nano cage structure of the glycidyl POSS serves as a rigid segment, and the epoxy resin softened at high temperature serves as a soft segment, forming a synergistic effect of the soft and hard segments, and in the fracture process, the crack encounters the glycidyl POSS to change its extension path, thereby preventing internal fracture, thereby improving the toughness and strength of the epoxy resin, and at the same time, due to the inherent high transparency and dispersion of the glycidyl POSS, the transparency of the epoxy resin can be improved; further, in the glycidyl POSS, the glycidyl POSS is used as a rigid segment, and the epoxy resin softened at high temperature is used ... cracking process, the crack encounters the glycidyl POSS to change its extension path, thereby preventing internal fracture, thereby improving the toughness and strength of the epoxy resin, and at the same time, due to the inherent high transparency and dispersion of the glycidyl POSS, the transparency of the epoxy resin can be improved; further, in the glycidyl POSS, the glycidyl POSS is used as a rigid segment, and the epoxy resin softened at high temperature is used as a soft segment, and the glycidyl POSS is used as a soft segment, and the glycidyl POSS is used as a soft segment, and the g A tetrapolymer and 4,4'-dithiodiphenylamine are grafted onto the water glyceryl POSS, thereby forming a composite modifier containing glyceryl POSS, a fluorinated alkyl chain, a flexible alkyl chain, and a dynamic disulfide bond long chain. The composite modifier is introduced into the side chain of the epoxy resin in the form of chemical grafting. The side chain is cross-linked with the main chain of the epoxy resin, and a large number of polar groups and hydrogen bonds are introduced to improve the moisture and heat resistance, toughness, heat resistance, and adhesion of the epoxy resin. In addition, the CF bond in the fluorinated alkyl chain has excellent resistance to ultraviolet aging, so that the anti-ultraviolet performance of the epoxy resin is improved. Therefore, the modified epoxy resin of the present invention has excellent transparency, weather resistance, adhesion and mechanical properties.

[0037] Tetrakis(3-mercaptopropionic acid) pentaerythritol ester belongs to the polythiol epoxy curing agent, which has the advantages of short curing time and high transparency. The present invention performs chain extension modification on the mercapto group of tetrakis(3-mercaptopropionic acid) pentaerythritol ester to form an intermediate product A, the molecular chain of the intermediate product A becomes longer, and non-polar benzene ring side groups are introduced into the molecule, so that the curing reaction is more complete, the cross-linking density is increased, and the bonding performance, moisture and heat resistance, heat resistance and mechanical properties of the adhesive are improved; the intermediate product A is mixed with 4,5-diaminobenzene-1,2 -Diphenol reacts to form intermediate product B, which is then combined with surface-modified nano zinc oxide to form an organic-inorganic hybrid curing agent. While further extending the chain to increase the cross-linking density, catechol structure and dynamic imine bond are introduced. The catechol structure and nano zinc oxide play the role of organic and inorganic ultraviolet absorbers, thereby improving the comprehensive performance of the adhesive (especially the anti-ultraviolet performance); in addition, the nano zinc oxide is combined in the form of chemical bonds to improve the dispersibility of the nano zinc oxide, thereby making the adhesive have better transparency and weather resistance.

[0038] In summary, the modified epoxy resin of the present invention is mixed with an organic-inorganic hybrid curing agent and then mixed with a transparent accelerator DMP-30, which can be quickly cured at room temperature to form a weather-resistant transparent adhesive with excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1This is a process flow chart of the preparation method of the weather-resistant transparent adhesive of the present invention;

[0040] Figure 2 It is a comparison chart of lap shear strength test of the weather-resistant transparent adhesives prepared in Examples 2-4 of the present invention and Comparative Examples 1-5 under different conditions;

[0041] Figure 3 It is a comparison chart of the yellowing resistance test of the weather-resistant transparent adhesives prepared in Examples 2-4 of the present invention and Comparative Examples 1-5;

[0042] Figure 4 It is a comparison chart of tensile strength test of weather-resistant transparent adhesives prepared in Examples 2-4 of the present invention and Comparative Examples 1-5;

[0043] Figure 5 It is a comparison chart of the fracture toughness test of the weather-resistant transparent adhesives prepared in Examples 2-4 of the present invention and Comparative Examples 1-5. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0045] Example 1

[0046] This embodiment discloses a method for preparing a composite modifier, comprising the following steps:

[0047] Step S1, 5.4 g acrylic acid, 5.1 g 1,4-pentadiene, 0.6 g dodecafluoroheptyl methacrylate, 9.6 g butyl acrylate, 0.09 g ammonium persulfate, and 90 g N,N-dimethylformamide were mixed, reacted at 80° C. for 3 h, and after the reaction was completed, centrifuged, washed, and dried to obtain a tetrapolymer;

[0048] 11 g of glycidyl POSS was added to a mixed solution of 80 g of ethanol and acetone, and stirred at room temperature until the mixed solution was colorless and transparent, and then 1.4 g of 1,4-butanedithiol and 1 g of triethylamine were added, and the mixture was heated to 80° C. and reacted for 6 h in a closed environment. After the reaction was completed, the mixture was distilled to obtain modified POSS; wherein the mixed solution of ethanol and acetone was obtained by mixing ethanol and acetone in a mass ratio of 3:1;

[0049] 13.8 g of the tetrapolymer and 0.8 g of azobisisobutyronitrile were added to 55 g of tetrahydrofuran, stirred until completely dissolved, heated to 60° C. in a nitrogen atmosphere, and 41.2 g of a modified POSS / tetrahydrofuran mixed solution with a concentration of 0.2 g / mL was added dropwise within 12 min under stirring, and the temperature was maintained at 60° C. for 6 h. After the reaction was completed, the reaction mixture was concentrated to one third of the original volume, and methanol was added to precipitate the product, which was filtered and dried to obtain graft-modified POSS;

[0050] Step S2, adding 7.5g of grafted modified POSS to 450g of methanol, ultrasonically treating for 35min, then adding 2.5g of 4,4'-dithiodiphenylamine, stirring for 15min, and then adding 15mL of 0.07g / mL 1-ethyl-(3-dimethylaminopropyl)carbodiimide / methanol solution at room temperature at a rate of 1mL / min while stirring, stirring the reaction for 24h, standing for 7h, filtering, washing, and drying to obtain a composite modifier.

[0051] Example 2

[0052] This embodiment discloses a method for preparing a weather-resistant transparent adhesive, comprising the following steps:

[0053] Step (1), adding 8.9 g of 4-(2,3-ethylene oxide)benzaldehyde to 400 g of ethyl acetate, stirring for 20 min to obtain a mixed solution; mixing 24.4 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 0.5 g of triethylamine, adding the mixed solution dropwise at a rate of 0.8 mL / min, heating to 65° C., stirring for reaction for 16 h, and rotary evaporation at 70° C. to obtain an intermediate product A;

[0054] 8.3 g of intermediate product A was added to 100 g of ethanol, stirred for 20 min, and then 3.5 g of 4,5-diaminobenzene-1,2-diphenol was added, heated to 60°C and stirred for 5 h. After the reaction was completed, the mixture was allowed to stand, centrifuged to remove the upper liquid, and the centrifuged precipitate was vacuum dried at 60°C for 12 h to obtain intermediate product B;

[0055] Step (2), preparing a zinc nitrate aqueous solution and a sodium carbonate aqueous solution with a concentration of 0.2 mol / L, adding the zinc nitrate aqueous solution to the sodium carbonate aqueous solution at a speed of 1 mL / min at a stirring speed of 400 r / min, filtering, washing the obtained white precipitate with distilled water for 3 times and then with ethanol, then vacuum drying at 90° C. for 8 h, and finally calcining at 300° C. for 2 h to obtain nano zinc oxide with an average particle size of 22.2 nm; wherein the volume ratio of the zinc nitrate aqueous solution to the sodium carbonate aqueous solution is 5:6;

[0056] Disperse 1 g of 3-glycidyloxypropyltrimethoxysilane and 10 g of nano zinc oxide in 100 g of ethanol, then reflux for 6 h at 75° C. and pH 4, collect and dry the precipitate to obtain surface-modified nano zinc oxide;

[0057] 8 g of surface-modified nano zinc oxide was added to 120 g of N,N-dimethylformamide, and ultrasonically treated for 30 min. Then 3 g of intermediate product B was added, and the mixture was heated to 75° C. and stirred for 26 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain an organic-inorganic hybrid curing agent.

[0058] Step (3), adding 1.5 g of the composite modifier to 100 g of N,N-dimethylformamide, stirring for 20 min, then adding 50 g of epoxy resin, reacting in a water bath at 75 ° C for 2.5 h, after the reaction is completed, removing the solvent by rotary evaporation at 75 ° C to obtain a modified epoxy resin;

[0059] The modified epoxy resin is used as component A; the organic-inorganic hybrid curing agent and the accelerator DMP-30 are mixed in a mass ratio of 1:0.03 as component B.

[0060] When using, mix component A and component B in a mass ratio of 1:1 and stir at a speed of 150r / min for 5 minutes.

[0061] Example 3

[0062] This embodiment discloses a method for preparing a weather-resistant transparent adhesive, comprising the following steps:

[0063] Step (1), adding 17.8 g of 4-(2,3-ethylene oxide)benzaldehyde to 500 g of ethyl acetate, stirring for 30 min to obtain a mixed solution; mixing 48.8 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 0.8 g of triethylamine, adding the mixed solution dropwise at a rate of 1.2 mL / min, heating to 75° C., stirring for reaction for 16 h, and rotary evaporation at 70° C. to obtain an intermediate product A;

[0064] 16.6 g of intermediate product A was added to 120 g of ethanol, stirred for 40 min, and then 7 g of 4,5-diaminobenzene-1,2-diphenol was added, heated to 75°C and stirred for reaction for 3 h. After the reaction was completed, the mixture was allowed to stand, centrifuged to remove the upper liquid, and the centrifuged precipitate was vacuum dried at 60°C for 12 h to obtain intermediate product B;

[0065] Step (2), preparing a zinc nitrate aqueous solution and a sodium carbonate aqueous solution with a concentration of 0.2 mol / L, adding the zinc nitrate aqueous solution to the sodium carbonate aqueous solution at a speed of 1.5 mL / min at a stirring speed of 500 r / min, filtering, washing the obtained white precipitate with distilled water for 5 times and then with ethanol, then vacuum drying at 100° C. for 6 h, and finally calcining at 350° C. for 2 h to obtain nano zinc oxide with an average particle size of 26.7 nm; wherein the volume ratio of the zinc nitrate aqueous solution to the sodium carbonate aqueous solution is 5:6;

[0066] 3 g of 3-glycidyloxypropyltrimethoxysilane and 12 g of nano zinc oxide were dispersed in 120 g of ethanol, and then refluxed for 4 h at 80° C. and pH 10, and the precipitate was collected and dried to obtain surface-modified nano zinc oxide;

[0067] 10 g of surface-modified nano zinc oxide was added to 150 g of N,N-dimethylformamide, and ultrasonically treated for 40 min. Then 5 g of intermediate product B was added, and the mixture was heated to 85° C. and stirred for reaction for 22 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain an organic-inorganic hybrid curing agent.

[0068] Step (3), adding 3.5 g of the composite modifier to 200 g of N,N-dimethylformamide, stirring for 30 min, then adding 80 g of epoxy resin, reacting in a water bath at 85° C. for 1.5 h, and after the reaction is completed, removing the solvent by rotary evaporation at 85° C. to obtain a modified epoxy resin;

[0069] The modified epoxy resin is used as component A; the organic-inorganic hybrid curing agent and accelerator DMP-30 are mixed in a mass ratio of 1:0.07 as component B.

[0070] When using, mix components A and B in a mass ratio of 1:1.25 and stir at a speed of 250 r / min for 2 minutes.

[0071] Example 4

[0072] This embodiment discloses a method for preparing a weather-resistant transparent adhesive, comprising the following steps:

[0073] Step (1), adding 13.4 g of 4-(2,3-ethylene oxide)benzaldehyde to 450 g of ethyl acetate, stirring for 25 min to obtain a mixed solution; mixing 36.6 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 0.7 g of triethylamine, adding the mixed solution dropwise at a rate of 1 mL / min, heating to 70° C., stirring for reaction for 18 h, and rotary evaporation at 75° C. to obtain an intermediate product A;

[0074] 12.5 g of intermediate product A was added to 110 g of ethanol, stirred for 30 min, and then 5.3 g of 4,5-diaminobenzene-1,2-diphenol was added, heated to 68°C and stirred for 4 h. After the reaction was completed, the mixture was allowed to stand, centrifuged to remove the upper liquid, and the centrifuged precipitate was vacuum dried at 60°C for 12 h to obtain intermediate product B;

[0075] Step (2), preparing a zinc nitrate aqueous solution and a sodium carbonate aqueous solution with a concentration of 0.2 mol / L, adding the zinc nitrate aqueous solution to the sodium carbonate aqueous solution at a speed of 1.2 mL / min at a stirring speed of 450 r / min, filtering, washing the obtained white precipitate with distilled water for 4 times and then with ethanol, then vacuum drying at 95° C. for 7 h, and finally calcining at 325° C. for 2 h to obtain nano zinc oxide with an average particle size of 24.9 nm; wherein the volume ratio of the zinc nitrate aqueous solution to the sodium carbonate aqueous solution is 5:6;

[0076] 2 g of 3-glycidyloxypropyltrimethoxysilane and 11 g of nano zinc oxide were dispersed in 110 g of ethanol, and then refluxed for 5 h at 82° C. and pH 7, and the precipitate was collected and dried to obtain surface-modified nano zinc oxide;

[0077] 9 g of surface-modified nano zinc oxide was added to 135 g of N,N-dimethylformamide, and ultrasonically treated for 35 min. Then, 4 g of intermediate product B was added, and the mixture was heated to 80° C. and stirred for reaction for 24 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain an organic-inorganic hybrid curing agent.

[0078] Step (3), adding 2.5 g of the composite modifier to 150 g of N,N-dimethylformamide, stirring for 25 min, then adding 65 g of epoxy resin, reacting in a water bath at 80° C. for 2 h, and after the reaction is completed, removing the solvent by rotary evaporation at 80° C. to obtain a modified epoxy resin;

[0079] The modified epoxy resin is used as component A; the organic-inorganic hybrid curing agent and the accelerator DMP-30 are mixed in a mass ratio of 1:0.05 as component B.

[0080] When used, components A and B were mixed in a mass ratio of 1:1.15 and stirred at a speed of 200 r / min for 3 minutes.

[0081] The composite modifier used in the above Examples 2-4 is the composite modifier prepared in Example 1.

[0082] Comparative Example 1

[0083] Compared with Example 4, in the process of preparing the modified epoxy resin in Comparative Example 1, the graft-modified POSS is used instead of the composite modifier, and other conditions remain unchanged.

[0084] Comparative Example 2

[0085] Compared with Example 4, in the process of preparing the modified epoxy resin in Comparative Example 2, POSS was used instead of the composite modifier, and other conditions remained unchanged.

[0086] Comparative Example 3

[0087] Compared with Example 4, in the process of preparing the weather-resistant transparent adhesive in Comparative Example 3, epoxy resin is used instead of modified epoxy resin, and other conditions remain unchanged.

[0088] Comparative Example 4

[0089] Compared with Example 4, in the process of preparing the organic-inorganic hybrid curing agent in Comparative Example 4, pentaerythritol tetrakis(3-mercaptopropionic acid) ester was used to replace the intermediate product B, and other conditions remained unchanged.

[0090] Comparative Example 5

[0091] Compared with Example 4, in Comparative Example 5, in the process of preparing the organic-inorganic hybrid curing agent, the intermediate product B is used to replace the organic-inorganic hybrid curing agent, and other conditions remain unchanged.

[0092] In the above embodiments and comparative examples, glycidyl POSS has a density of 1.25 g / mL, a viscosity of 4800 cp / 25°C, a refractive index of 1.51, an epoxy equivalent of 167, and a brand of Hybrid Plastics; epoxy resin E-51 is Phoenix brand epoxy resin E-51, with a solid content of 99% and a viscosity of 13000-16000 cp, and is from Jinan Sunny Chemical Technology Co., Ltd.; 4-(2,3-ethylene oxide)benzaldehyde, CAS No. 14697-49-5, a purity of 98%, is from Zhengzhou Weiyi Chemical Products Co., Ltd.; accelerator DMP-30, brand: Xinyu, CAS No. 90-70-2, an active ingredient content of 95%, and a liquid appearance, is from Jinan Xinyu New Materials Co., Ltd.

[0093] Experimental example

[0094] The performance of the weather-resistant transparent adhesives prepared in Examples 2-4 and Comparative Examples 1-5 was tested.

[0095] 1. Mechanical properties test: According to ASTM D638 standard, a tensile testing machine was used to test the mechanical properties of each group of samples at a loading rate of 2 mm / min.

[0096] 2. Adhesion performance test: According to GB / T 7124-2008, lap shear test was carried out to detect the adhesion performance of each group of samples at room temperature.

[0097] 3. Transparency: The transparency of each group of samples was tested by ultraviolet-visible spectrophotometry (UV-Vis, Analytik Jena, Germany).

[0098] 4. Weather resistance test:

[0099] (1) Hygrothermal aging: The sample was placed in a constant temperature and humidity test chamber at a temperature of 50°C and a relative humidity of 95% for 90 days, and the tensile shear strength was tested.

[0100] (2) Thermal aging: The specimens were immersed in a constant temperature water bath at 95°C for 7 days and the tensile shear strength was tested.

[0101] (3) Yellowing resistance: UV aging 30KWH / m 2 .

[0102] The test results are shown in Table 1:

[0103] Table 1

[0104]

[0105] It can be seen from the test results of Table 1 that the weather-resistant transparent adhesives prepared in Examples 2-4 of the present invention have high transparency, excellent mechanical strength, toughness, adhesion and weather resistance. From the comparison of Comparative Examples 1-2 and Example 4, it can be seen that the tetrapolymer and 4,4'-dithiodiphenylamine are grafted on the glycidyl POSS, a fluorinated alkyl chain, a flexible alkyl chain, and a dynamic disulfide bond are introduced, and the dispersibility of the glycidyl POSS can be improved, so that the modified epoxy resin has excellent transparency, weather resistance, adhesion and mechanical properties, thereby making the adhesive have excellent transparency, weather resistance, adhesion and mechanical properties; From the comparison of Comparative Example 3 and Example 4, it can be seen that the composite modifier of the present invention has excellent mechanical strength, toughness, adhesion and weather resistance due to the glycidyl POSS, tetrapolymer, 4,4'-dithiodiphenylamine, and the introduction of fluorinated alkyl chains, flexible alkyl chains, and dynamic disulfide bonds. The synergistic effect of thiodiphenylamine has a significant effect on improving the comprehensive performance of the adhesive; from the comparison of comparative example 4 and example 4, it can be seen that the intermediate product B is obtained by treating pentaerythritol tetrakis (3-mercaptopropionic acid), and the molecular chain of the intermediate product B becomes longer and a catechol structure and a dynamic imine bond are introduced, which can play a better curing effect and improve the comprehensive performance of the adhesive; from the comparison of comparative example 5 and example 4, it can be seen that due to the low addition amount of nano zinc oxide, it has almost no effect on the mechanical properties and adhesion of the adhesive, and due to its own small particle size, the adhesive has excellent transparency and yellowing resistance.

[0106] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A weather-resistant transparent adhesive, comprising component A and component B, characterized in that: Prepared by the following method: Step (1), 4-(2,3-ethylene oxide)benzaldehyde reacts with pentaerythritol tetrakis(3-mercaptopropionic acid) to obtain an intermediate product A; intermediate product A reacts with 4,5-diaminobenzene-1,2-diphenol to obtain an intermediate product B; Step (2), using zinc nitrate and sodium carbonate as raw materials to prepare nano zinc oxide; Nano zinc oxide is surface-modified by 3-glycidyloxypropyltrimethoxysilane and grafted with intermediate product B to obtain an organic-inorganic hybrid curing agent; Step (3), modifying the epoxy resin with a composite modifier to obtain a modified epoxy resin; The modified epoxy resin is used as component A; the organic-inorganic hybrid curing agent and accelerator DMP-30 are mixed as component B; Wherein, the preparation method of the composite modifier comprises the following steps: Step S1, acrylic acid, 1,4-pentadiene, dodecafluoroheptyl methacrylate, and butyl acrylate are polymerized to obtain a tetrapolymer; glycidyl POSS and 1,4-butanedithiol are reacted to obtain modified POSS; the tetrapolymer is reacted with the modified POSS to obtain a grafted modified POSS; Step S2: reacting the graft-modified POSS with 4,4'-dithiodiphenylamine to obtain a composite modifier.

2. The method for preparing the weather-resistant transparent adhesive according to claim 1, characterized in that: In the step (1), the preparation method of the intermediate product A is as follows: 4-(2,3-ethylene oxide)benzaldehyde is added to ethyl acetate, and stirred for 20-30 minutes to obtain a mixed solution; after mixing pentaerythritol tetrakis(3-mercaptopropionate) and triethylamine, the mixed solution is added dropwise at a rate of 0.8-1.2 mL / min, the temperature is raised to 65-75°C, the reaction is stirred for 16-20 hours, and the intermediate product A is obtained by rotary evaporation at 70-80°C; wherein the mass ratio of 4-(2,3-ethylene oxide)benzaldehyde, ethyl acetate, pentaerythritol tetrakis(3-mercaptopropionate) and triethylamine is (8.9-17.8):(400-500):(24.4-48.8):(0.5-0.8).

3. The method for preparing the weather-resistant transparent adhesive according to claim 1, characterized in that: In the step (1), the preparation method of the intermediate product B is as follows: the intermediate product A is added to ethanol, stirred for 20-40 minutes, and then 4,5-diaminobenzene-1,2-diphenol is added, heated to 60-75°C and stirred for reaction for 3-5 hours. After the reaction is completed, the mixture is allowed to stand, centrifuged, and dried to obtain the intermediate product B; wherein the mass ratio of the intermediate product A, ethanol, and 4,5-diaminobenzene-1,2-diphenol is (8.3-16.6):(100-120):(3.5-7).

4. The method for preparing the weather-resistant transparent adhesive according to claim 1, characterized in that: In the step (2), the preparation method of the nano zinc oxide is as follows: preparing a zinc nitrate aqueous solution and a sodium carbonate aqueous solution with a concentration of 0.2 mol / L each, adding the zinc nitrate aqueous solution to the sodium carbonate aqueous solution at a speed of 1-1.5 mL / min at a stirring speed of 400-500 r / min, filtering, washing, drying, and finally calcining at 300-350° C. for 2 h to obtain nano zinc oxide with an average particle size of 22.2-26.7 nm; wherein the volume ratio of the zinc nitrate aqueous solution to the sodium carbonate aqueous solution is 5:

6.

5. The method for preparing the weather-resistant transparent adhesive according to claim 1, characterized in that: In the step (2), the preparation method of the organic-inorganic hybrid curing agent is: 3-glycidyloxypropyltrimethoxysilane, nano zinc oxide, and ethanol are mixed in a mass ratio of (1-3):(10-12):(100-120), and then refluxed at 75-80° C. and a pH value of 4-10 for 4-6 hours, and the precipitate is collected and dried to obtain surface-modified nano zinc oxide; Add surface-modified nano zinc oxide to N,N-dimethylformamide, perform ultrasonic treatment for 30-40 minutes, then add intermediate product B, heat to 75-85°C, stir and react for 22-26 hours, filter, wash and dry after the reaction to obtain an organic-inorganic hybrid curing agent; wherein the mass ratio of surface-modified nano zinc oxide, N,N-dimethylformamide and intermediate product B is (8-10):(120-150):(3-5).

6. The method for preparing the weather-resistant transparent adhesive according to claim 1, characterized in that: In the step (3), the preparation method of the modified epoxy resin is as follows: adding the composite modifier to N,N-dimethylformamide, stirring for 20-30 minutes, then adding the epoxy resin, reacting in a water bath at 75-85°C for 1.5-2.5 hours, and after the reaction is completed, removing the solvent by rotary evaporation at 75-85°C to obtain the modified epoxy resin; wherein the mass ratio of the composite modifier, N,N-dimethylformamide, and epoxy resin is (1.5-3.5):(100-200):(50-80).

7. The method for preparing the weather-resistant transparent adhesive according to claim 1, characterized in that: In the step (3), the mass ratio of the organic-inorganic hybrid curing agent to the accelerator DMP-30 is 1:(0.03-0.07); the mass ratio of component A to component B is 1:(1-1.25); and the stirring condition is: stirring at a speed of 150-250 r / min for 2-5 min.

8. The method for preparing the weather-resistant transparent adhesive according to claim 1, characterized in that: In the step (3), the preparation method of the composite modifier is: Step S1, mixing acrylic acid, 1,4-pentadiene, dodecafluoroheptyl methacrylate, butyl acrylate, ammonium persulfate, and N,N-dimethylformamide in a mass ratio of (3.6-7.2):(3.4-6.8):(0.3-0.8):(6.4-12.8):(0.07-0.1):(80-100), reacting at 70-90° C. for 2-4 hours, centrifuging, washing, and drying after the reaction to obtain a tetrapolymer; Add glycidyl POSS to a mixed solution of ethanol and acetone, stir at room temperature until the mixed solution is colorless and transparent, then add 1,4-butanedithiol and triethylamine, heat to 75-85°C in a closed environment and react for 5-7h, and after the reaction is completed, distill to obtain modified POSS; wherein the mixed solution of ethanol and acetone is obtained by mixing ethanol and acetone in a mass ratio of 3:1; the mass ratio of glycidyl POSS, the mixed solution of ethanol and acetone, 1,4-butanedithiol, and triethylamine is (10-12):(60-100):(1.2-1.5):(0.8-1.2); Add the tetrapolymer and azobisisobutyronitrile to tetrahydrofuran, stir until the solid is completely dissolved, heat to 55-65°C in a nitrogen atmosphere, and dropwise add a modified POSS / tetrahydrofuran mixture with a concentration of 0.2 g / mL within 10-15 minutes under stirring, keep the temperature unchanged and react for 5.5-6.5 hours. After the reaction is completed, concentrate the reaction mixture to one third of the original volume, add methanol to precipitate the product, filter, and dry to obtain graft-modified POSS; wherein the mass ratio of the tetrapolymer, azobisisobutyronitrile, tetrahydrofuran, and modified POSS / tetrahydrofuran mixture is (9.2-18.4):(0.5-1.0):(40-70):(27.5-55); Step S2, adding the grafted modified POSS to methanol, ultrasonically treating for 30-40 minutes, then adding 4,4'-dithiodiphenylamine, stirring for 10-20 minutes, and then dripping 1-ethyl-(3-dimethylaminopropyl)carbodiimide / methanol solution with a concentration of 0.07 g / mL at a rate of 0.8-1.2 mL / min while stirring at room temperature, stirring for 22-26 hours, standing for 6-8 hours, filtering, washing, and drying to obtain a composite modifier; wherein the amount ratio of the grafted modified POSS, methanol, 4,4'-dithiodiphenylamine, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide / methanol solution is (5-10) g:(400-500) g:(1.5-3.5) g:(10-20) mL.

9. A weather-resistant transparent adhesive prepared by the method for preparing a weather-resistant transparent adhesive as claimed in any one of claims 1 to 8.

10. Use of the weather-resistant transparent adhesive according to claim 9 in bonding weather-resistant and wear-resistant transparent films and color-coated plates.

Citation Information

Patent Citations

  • High toughness epoxy adhesive

    CN101457132A

  • Weather-resistant epoxy adhesive

    CN103382378A

  • Epoxy resin composition good in transparency and application thereof to field of cars

    CN107090262A

  • Highly transparent UV-resistant epoxy resin adhesive and preparation method thereof

    CN110256990A

  • High-impact-resistance epoxy resin composite material synergistically toughened by modified zinc oxide and mercaptan and preparation method of high-impact-resistance epoxy resin composite material

    CN114940807A

Cited By

  • Renewable adsorbent for removing heavy metal ions and preparation method thereof

    CN119869469A

  • A renewable adsorbent for heavy metal ion removal and its preparation method

    CN119869469B

  • Benzene ring modified polythiol epoxy curing agent, preparation method thereof and application of benzene ring modified polythiol epoxy curing agent in epoxy resin adhesive

    CN120309570A

  • A benzene ring modified polythiol epoxy curing agent, a preparation method thereof and application thereof in an epoxy resin adhesive

    CN120309570B